OPTIMASI PARAMETER ANALITIK BIOSENSOR UREA BERBASIS IMMOBILISASI UREASE DALAM MEMBRAN POLIANILIN - Begum Fauziyah (SAINSTIS, 2011)
Biosensor Urea is made from the way immobilization enzyme urase inside of membrane polianilin with adsorption technique. Analytical parameter optimation from biosensor has done. The biggest difference between analit solution and blanko solution get in pH 7, long wave 580 nm and urease/PAn membrane having big difference intensity in optimum pH (pH 7) is urease/PAn membrane with urease variance 1 mg/mL. The result of characterization urease/PAn membrane as biosensor are concentration connection to absorban urease/PAn having correlation coefficient 0.9863; sensitivity 0.0445; detection limitation 0.6 ppm; variation coefficient (Kv) less than 5% with response around 20 minute. Urease/PAn membrane has stability till 7 days with 6 days of daily measuring repetitions. Key Words : polianilin, urease, urea, biosensor